Instrumentos De Valoración De Morbilidad Materna Extrema Y Su Aplicación En El Cuidado De Enfermería. Revisión Integrativa De La Literatura (2021)
Extreme maternal morbidity is one of the most frequent causes of mortality in pregnant women. in the world and in Colombia, for which it is necessary to distinguish between tools that enable the health team, especially the nursing professional; the identification of risk factors that predispose to this serious condition, at different times of the gestation through the use of assessment scales; and likewise, in light of the findings that provide these instruments, it is possible to analyze carefully that will help reduce this problem. The present work is a literature review that finally exposes some of the scales used in Latin America to determine risk factors or indicators of morbidity extreme mother in pregnant women. First, a contextualization is made from the conceptual, historical, legal point of view of extreme maternal morbidity; Secondly, to respond to the general objective of this document, which is to identify the instruments assessment of extreme maternal morbidity applied by the nursing professional in his exercise of care for pregnant women, an exhaustive search of articles was carried out indexed or degree theses in different databases such as Pubmed, Medigraphic, Scielo, among others., which made it possible to determine what instruments exist around the valuation of pregnant women in three moments: prenatal control, treatment of specific diseases and when the pregnant woman already has extreme maternal morbidity requiring management specialized in ICU to avoid complications. Practice guides are also included. clinic for its level of scientific evidence